2018
DOI: 10.1186/s13019-018-0790-x
|View full text |Cite
|
Sign up to set email alerts
|

Suture fixation of tracheal stents for the treatment of upper trachea stenosis: a retrospective study

Abstract: BackgroundStent migration is a common complication in treating trachea stenosis. There is no report concerning suture fixation of tracheal stent. The aim of this study was to investigate whether suture fixation of tracheal stent could avoid stent migration in patients with upper trachea stenosis. The complications were further investigated.MethodsThe patients with upper trachea stenosis who underwent tracheal stent placement for benign/malignant conditions in our hospital between May 2016 and April 2018 were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
9
0
2
Order By: Relevance
“…Following the resumption of operations, one patient with CTTS was referred to surgery after dilation and one patient with web-like stenosis was followed up with bronchoscopy after dilation. [16,18] Rigid bronchoscopy is the preferred procedure for massive or uncontrolled hemoptysis because of its advantage in securing the airway and providing ventilation. [19] In our study, 2 patients with hemoptysis underwent IBP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the resumption of operations, one patient with CTTS was referred to surgery after dilation and one patient with web-like stenosis was followed up with bronchoscopy after dilation. [16,18] Rigid bronchoscopy is the preferred procedure for massive or uncontrolled hemoptysis because of its advantage in securing the airway and providing ventilation. [19] In our study, 2 patients with hemoptysis underwent IBP.…”
Section: Discussionmentioning
confidence: 99%
“…One of 3 patients with PITS and stent migration was left to secondary healing and bronchoscopic follow-up, while the stents of the other two were sutured to the trachea to prevent migration recurrence. [16,18] Studies suggested two consecutive negative swab-PCR results prior to bronchoscopic procedures. In the first weeks of the pandemic period, bronchoscopy was performed if there was no clinical signs and if there was no finding compatible with CP in chest CT scans.…”
Section: Discussionmentioning
confidence: 99%
“…The advent of silicone stents for airway stenosis has increased the number of patients that can be managed through endoscopic means. External and internal fixation of these stents can decrease the rates of migration …”
Section: Discussionmentioning
confidence: 99%
“…In particular, stent migration has been commonly reported in the literature, ranging from 16–34% . Techniques to prevent migration include appropriate stent size, design of stents, or methods to secure the stent in place . Multiple techniques to endoscopically secure stents or keels exist, but these are oftentimes tedious and cumbersome, and can even require devoted surgical instruments (ie, Lichtenberger needle) .…”
Section: Introductionmentioning
confidence: 99%
“…It has been recommended, preferably to a metal stent or in those patients who are not a candidate for surgery (65,68). Although it has shown an improvement in symptoms (up to 100%) and a low migration rate (0 to 22%), it has never been popular due to having a difficult technique and a high rate of complication (55% stent and 100% external fixation related in one series) (65,(68)(69)(70)(71).…”
Section: A B D Cmentioning
confidence: 99%